Informed Consent As The Agreement In Therapeutic Contract Between Physician and Patient - Anggra Yudha Ramadianto (Universitas Sriwijaya, 2017)
The legal relationship between physician and patient in medical service is known as therapeutic contract. The therapeutic contract between physician/dentist and patient is based on two basic human rights, the right to self determination and the right to information. The principle of informed consent in medical service is based on the two basic human rights. In order to respect the patient’s autonomy there are five elements should be considered when executing the informed consent procedure. Those elements are competency, freedom, information, decision, and authorization. In the perspective of law of agreement informed consent as the patients’s agreement is a prerequirement in therapeutic contract that should be given based on patien’s freewill.